2015
DOI: 10.1111/clr.12722
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydroxyapatite granule size, porosity, and crystallinity on tissue reactionin vivo. Part A: synthesis, characterization of the materials, andSEManalysis

Abstract: The data from this study show that changing the size, porosity, and crystallinity of one HA-based bone substitute material can influence the integration of the biomaterials within the implantation site and the new bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 39 publications
2
51
1
Order By: Relevance
“…The figure includes Type I collagen for comparison purposes. Above 1300 cm −1 , almost all the bands are exclusively assigned to collagen vibrations, the exception being those brought about by CO 3 2− at 1460 cm −1 , and a broad band present at 3500, which is attributed to the presence of the structural OH- groups [12,45,46]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The figure includes Type I collagen for comparison purposes. Above 1300 cm −1 , almost all the bands are exclusively assigned to collagen vibrations, the exception being those brought about by CO 3 2− at 1460 cm −1 , and a broad band present at 3500, which is attributed to the presence of the structural OH- groups [12,45,46]. …”
Section: Resultsmentioning
confidence: 99%
“…However, no clear insight has yet been provided as to the exact relationship between the material properties of these calcium phosphate ceramics and their degradation behavior [12]. Therefore, long-term studies must be carried out to understand the pattern of biodegradation of xenografts and their influence on bone gain.…”
Section: Introductionmentioning
confidence: 99%
“…The figure includes Type I collagen for comparison purposes. Above 1300 cm -1 , almost all the bands are exclusively assigned to collagen vibrations, the exception being those brought about by CO3 2-at 1460 cm -1 , and a broad band present at 3500, which attributes to the presence of the structural OH-groups [12,45,46]. Figure 3 shows the xenograft materials before insertions for maxillary sinus floor elevation.…”
Section: Characterization Of Deproteinized Hydroxyapatite Materialsmentioning
confidence: 99%
“…However, no clear insight has yet been provided as to the exact relationship between the material properties of these calcium phosphate ceramics and their degradation behavior [12]. Therefore, long-term studies must be carried out to understand the pattern of biodegradation of xenografts and its influence on bone gain.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, Si-doped HA and Si-TCP ceramics have been prepared, although both pure Ca-P ceramics and Si-doped Ca-P ceramics still have shortcomings. Previous studies have shown that sintered HA does not significantly degrade, but remains a permanent fixture, susceptible to long-term failure [11,12,13]. Although α and β-TCP ceramics are degradable at a quicker degradation rate than HA, in vivo osteogenesis of sintered α and β-TCP ceramics is far from optimal.…”
Section: Introductionmentioning
confidence: 99%